Intervertebral disc regeneration: Influence of growth factors on differentiation of human mesenchymal stem cells (hMSC) - Ehlicke, F.; Freimark, D.; Heil, B.; Dorresteijn, A.; Czermak, Peter (Wichtig Editore, 2011)
Introduction: One common cause of disability in modern society is low back pain. The main reason for this pain is the degeneration of the intervertebral disc (IVD), particular of the nucleus pulposus (NP). For an early degeneration stage cell-based therapy would be a minimal invasive method of treatment. Therefore, adequate cells are needed. As the usage of NP cells is limited because of their insufficient amount or vitality, a promising alternative is the application of human mesenchymal stem cells (hMSCs). Objective: To investigate the potential of various growth factors to induce the differentiation of hMSCs into NP cells and thereby to obtain an alternative cell source for the treatment of IVD degeneration. Methods: hMSC-TERT were cultivated three-dimensionally in a hydrogel for 21 days to form NP cells. Cell survival and proliferation were determined using SybrGreen/propidium iodide double staining and the WST-test. To investigate the ability of several growth factors to differentiate hMSCs into NP cells, fluorescence immunostaining of NP-specific marker proteins (e.g. chondroadherin (CHAD) and the recently discovered cytokeratin 19 [1]) was performed. Results: Following the procedure described above, cells are able to maintain their viability and proliferation capacity throughout the cultivation time. By using a previously established immunofluorescence protocol, we could indicate the ability of three different growth factors to differentiate hMSCs into NP-like cells. Conclusion: The expression of several marker proteins in all differentiation experiments indicates the ability of IGF-1, FGF-2 and PDGF-BB to differentiate hMSCs into NP-like cells apart from the usually applied TGF-β3. Furthermore, our findings preclude the application of Cytokeratin 19 as a specific marker protein for NP cells [1]. Further experiments have to be done to find real specific NP marker proteins to indisputable verify the differentiation of hMSCs into NP cells. If so, application of the mentioned three growth factors would possibly be an option to obtain sufficient NP cells for minimal invasive IVD regeneration.
Keywords: Intervertebral disc regeneration; Differentiation; Growth factor; IGF-1; FGF-2; PDGF-BB